STRATEGI DAN METODE PEMBELAJARAN LITERASI NUMERASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DI SEKOLAH - Pratiwi, Adinda Dhea; Nurbaiti, Elsa Frida; Andalusia, Fairuz; Khoerunnisa, Hijri; Ramadhani, Moza Prameswari; Putri, Hafiziani Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning in schools faces challenges due to students' low numeracy literacy. This research examines effective strategies to improve understanding of mathematical concepts through a literature review. Results show that the integration of numeracy literacy with project-based thematic learning, Realistic Mathematics Education (RME), technology (including artificial intelligence), gamification, and contextual methods significantly improves students' numeracy and mathematical concepts. These strategies help students interpret and communicate numerical information in real contexts and improve problem-solving and critical thinking skills. Teachers are advised to apply varied and contextualized strategies for meaningful and relevant learning.